Integrasi Project-Based Assessment dalam Project-Based Learning untuk Mengembangkan Keterampilan Abad 21 Pembelajaran Akidah Akhlak di MTsN 9 Sleman - Mitha Shaskila Sinaga; Suwadi (Indonesian Journal of Action Research, 2026)
Purpose – This study aims to describe the implementation of Project-Based Assessment (PBA) in Project-Based Learning (PjBL) to develop 21st-century learning skills in akidah akhlak learning at MTsN 9 Sleman through the integration of Computational Thinking (CT), a deep learning approach, and the SOLO Taxonomy. Methods – This study employs a qualitative approach with a descriptive case study design. The selection of research subjects was carried out using a purposive sampling technique, based on specific considerations aligned with the needs of the study. The informants in this research consist of an Islamic education teacher (Akidah Akhlak) and five eighth-grade students. Data collection was conducted through interviews, classroom observations, and documentation studies. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and continuous conclusion drawing. Findings – The findings indicate that the implementation of PBA in PjBL integrated with CT, deep learning, and the SOLO Taxonomy provides a learning process that encourages students’ active engagement in developing 21st-century skills, including critical thinking, creativity, communication, and collaboration. Students were involved in various stages of learning, starting from problem identification, data collection, planning, project implementation, to reflection. This process demonstrated gradual and contextual development in cognitive, emotional, and social aspects. Assessment was conducted comprehensively through process assessment, product assessment, and reflection, enabling teachers to continuously monitor students’ learning progress.